2011
DOI: 10.1063/1.3573665
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous low-temperature contribution to the heat capacity from hybridized electronic states on transition element impurities

Abstract: An anomalous nonmonotonic contribution to the temperature dependence of the electron heat capacity of mercury selenide is detected. This is explained in terms of hybridized electronic states on donor impurities. The observed effect is described by a theory of electron heat capacity based on a quantum Fermi-liquid approach including localization and electron-electron interactions. A quantitative interpretation of the experimental dependences yields values for the parameters of the hybridized states that are con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Ferromagnetic (Ga,Mn)As DMS are p-type semiconductors so the logical assumption might be that in the thermal equilibrium the QW is populated with 2D holes which are spin-polarized due to coupling with Mn ions so that the light emitted from the QW would be circular polarized. The theory of this mechanism has been developed in 10,11 and it is probably relevant to the experimental data reported in 12,13 . However the recent time-resolved experiments on similar samples with more shallow In x Ga 1−x As QW have demonstrated that under moderate photoexcitation the spin polarization in GaMnAs-based hybrid is a non-equilibrium, dymanic effect 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Ferromagnetic (Ga,Mn)As DMS are p-type semiconductors so the logical assumption might be that in the thermal equilibrium the QW is populated with 2D holes which are spin-polarized due to coupling with Mn ions so that the light emitted from the QW would be circular polarized. The theory of this mechanism has been developed in 10,11 and it is probably relevant to the experimental data reported in 12,13 . However the recent time-resolved experiments on similar samples with more shallow In x Ga 1−x As QW have demonstrated that under moderate photoexcitation the spin polarization in GaMnAs-based hybrid is a non-equilibrium, dymanic effect 14 .…”
Section: Introductionmentioning
confidence: 99%
“…It further appeared that numerous examples of Fano resonances existed in atomic and nuclear physics, condensed matter physics and optics 2 . The co-existence of a localized discrete level and continuum of states within the same energy range is also quite common in low-dimensional semiconductor structures [2][3][4][5] . The structures containing a quantum well (QW) and a ferromagnetic or paramagnetic layer located in the vicinity of the QW nowadays are gaining a special interest as they are believed to combine the high mobility of the carriers in the QW and magnetic properties provided by the magnetic layer.…”
Section: Introductionmentioning
confidence: 99%
“…If A is determined from the experimental data, then it can be used to establish whether spin polarization of the electron system occurs. In our papers on the temperature dependences of the impurity contributions to the specific heat and the moduli of elasticity of crystalline mercury selenide crystals, 3,4 a detailed quantitative interpretation of the data has been used to determine the parameters (including A) of the hybridized states. This result, which presumably corresponds to the existence of spontaneous spin polarization of the hybridized states, has been discussed in Ref.…”
Section: Detecting Spontaneous Polarization Of Hybridized States In Imentioning
confidence: 99%
“…Here we give a more detailed justification of the analysis of the experimental data 3,4 and then consider a theoretical argument for the feasibility of direct observation of spontaneous spin polarization of conduction electrons in experiments on the anomalous Hall effect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation